Analisis Faktor Determinan Kejadian Hipertensi Di Kota Banjar Baru Tahun 2024 - parellangi, andi; Prayogi, Bisepta; Rizani, Khairir; Utama, Richo Dharmadi (Politeknik Kementerian Kesehatan Banjarmasin, 2025)
Hypertension is a disease with high prevalence, so it can affect a person's quality of life and productivity. This disease has killed 9.4 million people worldwide each year. In South Kalimantan Province, hypertension is the third highest cause of maternal mortality, with a figure of 23%. The purpose of this study was to analyze the determinant factors of hypertension in Banjarbaru City. This study was conducted in the Health Center Area in Banjarbaru City, South Kalimantan. The population used was all Banjarbaru residents who had hypertension, and while the sampling technique used was random sampling, the research sample was 50 people who had hypertension. Statistical results obtained that several things that can be determinant factors in hypertension sufferers are age category (p-value: 0.025), genetic factors (p-value: 0.040), nutritional status (p-value: 0.003), coffee consumption patterns (p-value: 0.031), vegetable consumption patterns (p-value: 0.034), salt consumption patterns (p-value: 0.006), sleep patterns (p-value: 0.001), stress levels (p-value: 0.041), exercise habits (p-value: 0.000), comorbidities (p-value: 0.031), and compliance with taking medication (p-value: 0.000). It is hoped that this can be the basis for a cooperation program for all parties in designing rules and policies for early prevention of hypertension